Evaluation of H.265 Video Delivery Based on Dynamic Adaptive Streaming over HTTP (DASH) Using Mobile Devices - Hamid Azwar (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2017)
MPEG Dynamic Adaptive Streaming over HTTP (MPEG-DASH) is a standard for HTTP streaming that allows interoperability between servers and clients from different vendors which is able to adjust the speed of video delivery to changing bandwidth. Today there is the latest H.265 video coding known as the High Efficiency Video Coding (HEVC). This research implemented the delivery of the H.265 video through the method of Dynamic Adaptive Streaming over HTTP (DASH) using mobile devices. The test was conducted by sending videos over 3G networks with GSM length video segment consists of 2 seconds, 5 seconds, 10 seconds and 20 seconds. The video quality provided in this study consisted of 5 video levels with different bit rates. From the test results, the submitted videos using a smaller video segment generated greater throughput and acquired more video quality with a higher bit rate than the video to a larger segment. Video delivery with segment of 2 seconds acquired video quality with the highest level of 83%, meanwhile the video delivery segment of 20 seconds obtained video quality with the highest level of 33%.